Predictors of Treatment Failure among Adult Antiretroviral Treatment (ART) Clients in Bale Zone Hospitals, South Eastern Ethiopia. - Demewoz Haile; Abulie Takele; Ketema Gashaw; Habtamu Demelash; Dabere Nigatu (PLoS ONE, 2016)
BACKGROUND:Treatment failure defined as progression of disease after initiation of ART or when the anti-HIV medications can't control the infection. One of the major concerns over the rapid scaling up of ART is the emergence and transmission of HIV drug resistant strains at the population level due to treatment failure. This could lead to the failure of basic ART programs. Thus this study aimed to investigate the predictors of treatment failure among adult ART clients in Bale Zone Hospitals, South east Ethiopia. METHODS:Retrospective cohort study was employed in four hospitals of Bale zone named Goba, Robe, Ginir and Delomena. A total of 4,809 adult ART clients were included in the analysis from these four hospitals. Adherence was measured by pill count method. The Kaplan Meier (KM) curve was used to describe the survival time of ART patients without treatment failure. Bivariate and multivariable Cox proportional hazards regression models were used for identifying associated factors of treatment failure. RESULT:The incidence rate of treatment failure was found 9.38 (95% CI 7.79-11.30) per 1000 person years. Male ART clients were more likely to experience treatment failure as compared to females [AHR = 4.49; 95% CI: (2.61-7.73)].Similarly, lower CD4 count (<100 m3/dl) at initiation of ART was found significantly associated with higher odds of treatment failure [AHR = 3.79; 95% CI: (2.46-5.84).Bedridden [AHR = 5.02; 95% CI: (1.98-12.73)] and ambulatory [AHR = 2.12; 95% CI: (1.08-4.07)] patients were more likely to experience treatment failure as compared to patients with working functional status. TB co-infected clients had also higher odds to experience treatment failure [AHR = 3.06; 95% CI: (1.72-5.44)]. Those patients who had developed TB after ART initiation had higher odds to experience treatment failure as compared to their counter parts [AHR = 4.35; 95% CI: (1.99-9.54]. Having other opportunistic infection during ART initiation was also associated with higher odds of experiencing treatment failure [AHR = 7.0, 95% CI: (3.19-15.37)]. Similarly having fair [AHR = 4.99 95% CI: (1.90-13.13)] and poor drug adherence [AHR = 2.56; 95% CI: (1.12-5.86)]were significantly associated with higher odds of treatment failure as compared to clients with good adherence. CONCLUSION:The rate of treatment failure in Bale zone hospitals needs attention. Prevention and control of TB and other opportunistic infections, promotion of ART initiation at higher CD4 level, and better functional status, improving drug adherence are important interventions to reduce treatment failure among ART clients in Southeastern Ethiopia.